Implementasi Supervisi Akademik Kepala Sekolah dalam Meningkatkan Kinerja Pendidik - Ujang Yosep Ayubi; Much. Tsulutsallaily Syahmuntaqy; Ari Prayoga (MANAZHIM, 2020)
The effectiveness and intensity of principals in carrying out supervision to educators has limitations in terms of the division of tasks and time. This study aims to uncover the implementation of school principals' academic supervision in order to improve the performance of Educators in Assalaam Vocational High Schools (SMK) in Bandung, Indonesia. The research method used in this study is a qualitative method with a descriptive approach. Data collection techniques in this study used structured interviews with key informants for school principals, educators; participatory observation of supervision activities, and documentation of documents related to academic supervision. The results showed that the academic supervision process was carried out using two methods, firstly, the usual method (outside the classroom) was conducted conditionally and secondly, the clinical method (in class), carried out on a scheduled basis by the school principal or vice-principal through three stages namely, planning stage, implementation phase and evaluation stage. Educators provide a positive response to the implementation of academic supervision.